2012
DOI: 10.18517/ijaseit.2.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rainfall on Traffic Stream Characteristics during Peak and Non-Peak Periods

Abstract: This paper examined the effect of rainfall on traffic stream behaviour during peak and non-peak periods on a basic highway section. Data on this section which is located on the J5 was collected for four months during which 99 rainfall events occurred. The traffic consisted of 75.80% cars, 10.23% motorcycles, 3.51% trucks and 10.46% of other vehicles. Traffic was observed for both rain and no-rain conditions and the data was analysed to see the effect of the rain. The results showed decreases in the speed as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, they concluded that the larger PCU values with higher standard deviations observed under dry conditions resulted from lacking sufficient sample size. In another research effort in Asia, Alhassan and Ben-Edigbe found that PCE values decreased with an increase in rainfall intensity in a highway section in Malaysia ( 11 ).…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…However, they concluded that the larger PCU values with higher standard deviations observed under dry conditions resulted from lacking sufficient sample size. In another research effort in Asia, Alhassan and Ben-Edigbe found that PCE values decreased with an increase in rainfall intensity in a highway section in Malaysia ( 11 ).…”
Section: Literature Reviewmentioning
confidence: 96%
“…In addition, the combined impact of RW conditions and traffic composition—that is, HV ratio—has not been studied adequately. Yet, there is concensus that HVs noticeably influence traffic parameters as a result of their larger vehicle size and limited maneouverability ( 4 , 11 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Round-top since the working days in Johor are between Sunday and Thursday. During off-peak hours, there is more likely to be free traffic flow and, consequently, fewer interactions between vehicles [24].…”
Section: Sinusoidalmentioning
confidence: 99%
“…Mukhlas et al (2016) [15] stated that increase in rainfall intensity leads to speed and capacity reduction. In a study carried out by Alhassan and Ben-Edigbe (2012) [16], capacity loss of 1.08%, 6.27% and 29.25% was reported for light, moderate and heavy rain, respectively. Capacity by its definition is stochastic, meaning it has no set value.…”
Section: Introductionmentioning
confidence: 99%